2007
DOI: 10.1136/ard.2007.081612
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal dilatation on high-resolution computed tomography scan of the lungs as a sign of scleroderma

Abstract: Oesophageal dilatation as visible on an HRCT scan of the chest may alert doctors to look for other signs or symptoms of SSc in these patients, enabling early diagnosis and specific treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 25 publications
3
39
0
3
Order By: Relevance
“…It is well known that the esophagus is dilated in systemic sclerosis (Bhalla et al 1993;Pitrez et al 2006;Vonk et al 2008;Patiwetwitoon et al 2012), but its precise measurements and association with lung disease had not been done before. The finding of retained food and liquid also indicates esophageal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that the esophagus is dilated in systemic sclerosis (Bhalla et al 1993;Pitrez et al 2006;Vonk et al 2008;Patiwetwitoon et al 2012), but its precise measurements and association with lung disease had not been done before. The finding of retained food and liquid also indicates esophageal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The CT image of esophagus, if correlated with function, has several practical advantages over conventional methods to evaluate esophageal dysfunction: availability, noninvasiveness, easy repeatability, and little need of patient cooperation. However, previous studies demonstrated conflicting results in the correlation between esophageal dilation on CT and interstitial lung disease in systemic sclerosis patients (Vonk et al 2008;Patiwetwitoon et al 2012).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations